Honeypot in Information System Security - Shoba, N; Sathya, V (International Journal of Computer Sciences and Engineering, 2025)
This days security in information system is very challenging , so security for network security plays a vital role in all fields. A honeypot is a network-attached system set up as a decoy to lure cyberattackers and to detect, deflect or study hacking attempts in order to gain unauthorized access to information systems. The function of a honeypot is to represent itself on the internet as a potential target for attackers – usually a server or other high-value target – and to gather information and notify defenders of any attempts to access the honeypot by unauthorized users. Honeypot is a well designed system that attracts hackers into it. By luring the hacker into the system, it is possible to monitor the processes that are started and running on the system by hacker. In other words, honeypot is a trap machine which looks like a real system in order to attract the attacker. The aim of the honeypot is analyzing, understanding, watching and tracking hacker’s behaviours in order to create more secure systems. Honeypot is great way to improve network security administrators’ knowledge and learn how to get information from a victim system using forensic tools. Honeypot is also very useful for future threats to keep track of new technology attacks.